PENGARUH PELATIHAN DAN BUDAYA KERJA TERHADAP KINERJA KARYAWAN DEALER DAN BENGKEL PADA PT. KOKO JAYA PRIMA DI MAKASSAR - Hj. Salmiaty Taty (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2016)
This study aims to determine the effect of training and work culture on employee performance and bengkelpada dealer PT. Prima Jaya Makassar Koko and analyze the extent of influence of training and work culture affects employee performance in PT dealers and repair shops. Prima Jaya Koko in Makassar. With the method used is descriptive analysis is an analysis that describes the responses of respondents regarding the effect of training and work culture on employee performance, obtained by respondents from questionnaires distributed and multiple linear regression analysis is an analysis to determine how the state or the influence of training and work culture on employee performance. The results of the discussion of this study showed that the variables of training and work culture affect the performance of employees at PT Koko Jaya Prima in Makassar, the variable training and work culture were included as independent variables, it was found that the variable work culture most affect the performance of employees at PT Koko Jaya Prima Makassar, the dependent variable is the performance of employees who studied the performance of employees at PT. Prima Jaya Koko is good because it is supported by the training and work culture.